Evaluation of User Interfaces Description Languages to Augmented Reality - Cruz-Carrizales, Camilo-Andrés; Bautista-Rojas, Luis-Eduardo; Pedraza-Ferreira, Gabriel-Rodrigo (Revista Facultad de Ingeniería, 2021)
Augmented reality is a rapidly advancing technology as it is widely used in several applications and domains, from the aerospace industry to medical-surgical applications, particularly in learning and training. A fundamental part of the educational use is the graphical user interface as a vehicle to deliver information to students. Within the augmented experiences development process, it is necessary to identify the most appropriate way to describe the user interface. This article evaluates languages describing augmented reality user interfaces. In this paper, several languages are analyzed, and new criteria are proposed to extend the evaluation framework. Finally, the results show the current limitations and the slowdown of development and adaptation of new languages for augmented reality platforms.